Regulation of Apoptosis and Cell Cycle Activity in Rheumatoid Arthritis - Perlman, H.; Pagliari, L.J.; Volin, M.V. (Current Molecular Medicine, 2001)
The regulation of proliferation and cell death is vital for homeostasis, but the mechanisms that coordinately balances these two events in rheumatoid arthritis (RA) remains largely unknown. In RA, the synovial lining increases through enhanced proliferation, migration, and / or decreased cell death. The aberrant decrease in apoptosis or increased cell cycle activity of fibroblast-like or macrophage-like synoviocytes is responsible for the synovial hyperplasia and contributes to the destruction of cartilage and bone. Recently, numerous molecules that modulate apoptosis and cell cycle have been implicated to play a role in RA. This review will describe the current understanding of the molecular mechanisms that govern apoptosis and cell cycle and their relationship to RA pathogenesis.
Keywords: Rheumatoid Arthritis